Evaluasi Kualitas Layanan Website E-Commerce Salestock Indonesia Dengan Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis - Rizky Nanda Istichomah; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The quality of the web service Salestockindonesia.com needs to be evaluated because it has a ranking of 1591 according to alexa.com, ranked 422 according to similiarweb.com and ranked 72 according to statshow.com which can be stated far below similar websites. Evaluation is done by using Webqual variable that is usability, information quality, and service interaction quality. Usability there are six indicators, information quality there are four indicators, and service interaction quality there are three indicators. Data quality of service obtained from questionnaire which then the result is analyzed by using method of Importance Performance Analysis (IPA). Data obtained from the number of samples of 100 respondents by using questionnaires. From the evaluation results can be stated that the quality of service on the variable usability of two indicators of good quality that is on the indicators of ease of us and navigation and learnability. Four indicators of poor quality that is on the indicator of appearance, the imaged conveyed to the user, errors, and satisfaction. In variable information quality two indicators of good quality that is on indicator of relevance and accessibility. Two quality variables are less good that is on indicators of representational and accuracy. In service interaction quality variable two good quality indicator that is at indicator of trust and responsiveness and one indicator of quality is not good that is at empathy indicator. From the results of these tests the authors provide recommendation improvement for the poor quality that is referenced from the relevant journal or scientific articles.